Impact of cell cycle dynamics on pathology recognition: Raman imaging study. Issue 2 (25th October 2018) - Czamara, Krzysztof; Karnas, Elzbieta; Majka, Zuzanna; Wojcik, Tomasz; Zuba‐Surma, Ewa K.; Baranska, Malgorzata; Kaczor, Agnieszka
Abstract : Confocal Raman imaging combined with fluorescence‐activated cell sorting was used for in vitro studies of cell cultures to look at biochemical differences between the cells in different cell phases. To answer the question what is the impact of the cell cycle phase on discrimination of pathological cells, the combination of several factors was checked: a confluency of cell culture, the cell cycle dynamics and development of pathology. Confluency of 70% and 100% results in significant phenotypic cell changes that can be also diverse for different batches. In 100% confluency cultures, cells from various phases become phenotypically very similar and their recognition based on Raman spectra is not possible. For lower confluency, spectroscopic differences can be found between cell cycle phases (G0 /G1, S and G2 /M) for control cells and cells incubated with tumor necrosis factor alpha (TNF‐α), but when the mycotoxin cytochalasin B is used the Raman signatures of cell phases are not separable. Generally, this work shows that heterogeneity between control and inflamed cells can be bigger than heterogeneity between cell cycle phases, but it is related to several factors, and not always can be treated as a rule. Abstract : Cell division is an extremely important cellular event introducing natural inhomogeneity in cell populations. Biochemical changes associated with different cell cycle phases undoubtedly have influence on experimental results. In this work, we present studies on the multi‐factor impact of cell cycle on discrimination of pathological cells in in vitro model of cell cultures with the help of Raman imaging combined with fluorescence‐activated cell sorting.